2021
DOI: 10.3389/fcell.2020.607670
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53 Gain-of-Function: Role in Cancer Development, Progression, and Therapeutic Approaches

Abstract: Frequent p53 mutations (mutp53) not only abolish tumor suppressor capacities but confer various gain-of-function (GOF) activities that impacts molecules and pathways now regarded as central for tumor development and progression. Although the complete impact of GOF is still far from being fully understood, the effects on proliferation, migration, metabolic reprogramming, and immune evasion, among others, certainly constitute major driving forces for human tumors harboring them. In this review we discuss major m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
108
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 188 publications
(152 reference statements)
2
108
0
Order By: Relevance
“…Mutations of the tumor suppressor p53 are well established as being associated with approximately 50% of human cancers [ 235 , 236 , 237 , 238 , 239 ]. A panel of TNBC cell lines has been identified to express mutant p53 (mtp53) [ 240 ], which is commonly found in TNBC [ 120 , 192 ].…”
Section: Resistance To Anti-egfr Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations of the tumor suppressor p53 are well established as being associated with approximately 50% of human cancers [ 235 , 236 , 237 , 238 , 239 ]. A panel of TNBC cell lines has been identified to express mutant p53 (mtp53) [ 240 ], which is commonly found in TNBC [ 120 , 192 ].…”
Section: Resistance To Anti-egfr Therapeuticsmentioning
confidence: 99%
“…As mentioned earlier, p53 mutations are commonly found in TNBC [ 120 , 192 ]. Since p53 mutations result in gain-of-function as an oncogene as well as loss-of-function in terms of tumor suppressor function, targeting mtp53 or restoring wild-type p53 (wtp53) is a promising therapeutic option [ 239 ]. Notably, adenoviral-vector-expressing wtp53 (Ad-wtp53) was approved as the world’s first commercial gene therapy product by the Chinese regulatory authority [ 581 ].…”
Section: Combination Strategy For Overcoming Egfri Resistance In Tnbcmentioning
confidence: 99%
“…p53 mt deactivates sequence-specific DNA-binding activity, thereby causing the loss of normal p53 tumor suppressor function and the inability of the p53 wt heterodimer to form a tetramer complex, thereby damaging dimer function ( 22 ). In addition, p53 mt causes another ‘gain of function’ (GOF) that not only promotes tumor progression, migration and metabolism but also increases tumor cell resistance to radiotherapy ( 23 , 24 ). This outcome is ascribed to the upregulation of multiple genes by p53 mt , including phosphatase and tensin homolog, c-myc, NF-κB, p16 INK4A , p63 and p73 ( 25 30 ).…”
Section: P53 and Malignant Diseasementioning
confidence: 99%
“…This crucial observation was made by analyzing the TP53 locus in a series of 25 adenomas and 33 colorectal carcinomas. The authors' strategy comprised both the quantification of allelic deletions occurring in this locus and the sequencing of its exons 5 to 9, which correspond to its DNA-binding domain, where the vast majority of p53 mutations cluster in human cancers (3). Through these analyses, the authors found that in 90% of adenomas, both TP53 alleles were retained and did not have any mutations.…”
mentioning
confidence: 99%
“…The answer, the authors argued, must be that the mutation of TP53-rather than its simple loss-endows cancer cells with advantageous properties allowing tumors to become invasive. This was formally proven to be correct in 2004, when two laboratories led by Guillermina Lozano (4) and Tyler Jacks (5) generated mouse models mimicking the Li-Fraumeni syndrome, a disease caused by the somatic mutation of TP53 predisposing to the spontaneous onset of multiple tumor types, especially in children and young adults (3). Importantly, in contrast to Trp53 À/À mice, both Trp53 R172H/À and Trp53 R270H/À mice developed distinct tumors, including invasive and metastatic carcinomas (4, 5), thus confirming the hypothesis based on analysis of clinical samples.…”
mentioning
confidence: 99%